2021
DOI: 10.22159/ajpcr.2021.v14i1.40118
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Therapeutic Evaluation of the African Vegetables (Clerodendrum Volubile Leaf and Irvingia Gabonensis Seed Extracts) in Trastuzumab-Mediated Hepato-Renal Dysfunction in Wistar Rats

Abstract: Objective: The use of trastuzumab (TZM) in the clinical management of human epidermal growth factor receptor 2 positive metastatic breast and gastric cancers, gastro-esophageal adenocarcinoma, and colorectal carcinoma has been limited by its off-target cardiac, hepatic, and renal toxicities which till date have no effective therapies in either their prevention or amelioration. Thus, the present study is designed at investigating the protective and therapeutic potentials of 400 mg/kg/day Clerodendrum volubile e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 91 publications
(119 reference statements)
0
1
0
Order By: Relevance
“…Similarly, in another study investigated by Olorundare and colleagues, for the first time, ethanolic extract of C. volubile leaves significantly decreased trastuzumab (TZM)-induced cardiotoxicity in rats, and its cardioprotective effect was recorded to be facilitated through its antioxidant ability, which stimulates free radical scavenging and inhibits lipid peroxidation [ 127 ]. Also, Adeneye et al [ 128 ] confirmed the protective and therapeutic potentials of ethanolic extract of C. volubile leaves in trastuzumab-intoxicated Wistar rats. The findings corroborated the report of Molehin [ 129 ], who documented the ameliorative potential of methanolic extracts of C. volubile leaves against DOX-induced nephrotoxicity in rats.…”
Section: Pharmacological Potentials Of C Volubilementioning
confidence: 95%
“…Similarly, in another study investigated by Olorundare and colleagues, for the first time, ethanolic extract of C. volubile leaves significantly decreased trastuzumab (TZM)-induced cardiotoxicity in rats, and its cardioprotective effect was recorded to be facilitated through its antioxidant ability, which stimulates free radical scavenging and inhibits lipid peroxidation [ 127 ]. Also, Adeneye et al [ 128 ] confirmed the protective and therapeutic potentials of ethanolic extract of C. volubile leaves in trastuzumab-intoxicated Wistar rats. The findings corroborated the report of Molehin [ 129 ], who documented the ameliorative potential of methanolic extracts of C. volubile leaves against DOX-induced nephrotoxicity in rats.…”
Section: Pharmacological Potentials Of C Volubilementioning
confidence: 95%